Multi-Objective Optimal Control for Uncertain Singularly Perturbed Systems - Lei Liu; Shaofan Feng (IEEE Access, 2021)
This paper studies the passive multi-objective optimal control of uncertain singularly perturbed systems. First, the uncertainty is described in a norm-bounded way, and then the state space model of the system is determined. Further time, the problem of passivity can also be transformed into a linear quadratic performance index problem. According to the Lyapunov stability theory, the system robust stability criterion is derived, based on the above conclusion, the corresponding parameterized passive multi-objective controller is designed using state feedback, and the weight matrix and the minimum performance index are solved based on the optimal control theory. Finally, a numerical example is given to illustrate the correctness and feasibility of the control method.